GENERAL DESCRIPTION OF INTERACTIVE LEARNING. INTERACTIVE EDUCATION AND ITS DIDACTIC POSSIBILITIES - Kadyrova Muhayyokhon Solievna; Mamatkulova Feruzakhon Tokhirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
one of the important requirements for the organization of modern education is to achieve high results in a short time without spending too much mental and physical effort. Based on the delivery of specific theoretical knowledge to students in a short period of time, the formation of certain activity skills and competencies, control of their activities, assessment of the level of theoretical and practical knowledge acquired by them requests the teacher to educator high skills and a new approach to the educational process. requests. The article briefly covers these issues.